ANXIETY DISORDER AS AN INSPIRATION FOR CREATING PAINTINGS - Fanaza Apay Armita (Universitas Negeri Semarang, 2025)
This article explores how anxiety disorder functions as a conceptual and emotional foundation in contemporary painting, particularly within the artist’s personal creative practice. The study examines how persistent worry, social discomfort, emotional sensitivity, and intrusive thoughts can be transformed into symbolic visual elements through a studio-based method. By observing internal emotional experiences and translating them into sketches, compositions, and painterly experimentation, the artworks reveal expressive figures, confined spaces, repeated eye motifs, and contrasting color arrangements that reflect the complex psychological atmosphere of anxiety. The findings demonstrate that painting becomes not only a medium for aesthetic expression but also a reflective and therapeutic space where internal conflict can be processed, reinterpreted, and communicated. This research concludes that anxiety disorder can enrich artistic creation by generating emotionally charged visual narratives that resonate deeply with both the artist and the audience.